Mediko-biologiceskie problemy sportivnogo otbora professionalov - Kogan, O. S. (Teorija i Praktika fiziceskoj Kul'tury, 2003)
The raising of so-called "Sports of maximum achievements", involving a number of young people, demands the necessity of the constant and obligatory control of the state of their health and the adequateness of physical loadings offered to them. When selecting athletes to participate in the "Sports of maximum achievements" it is necessary to define the degree of their adaptation ability with the methods, allowing to estimate the cardiovascular and the nervous system activity while using the increased physical and psycho-emotional loadings. It is recommended to use the methods of cardiointervalography (CIG) and the galvanic skin reaction (GSR) as the useful selection criterion in the professional sport activity and as means of the functional state control of athletes in the various periods of their training process. The dynamical analysis of athletes adaptation ability with the means of CIG and GSR allows to prevent professional athletes from the pathological state development and to take timely measures for the professional pathology prophylactics.